Body size ideals and body satisfaction among Dutch-origin and African-origin residents of Amsterdam: The HELIUS study. - Jody C Hoenink; Henrike Galenkamp; Erik J Beune; Marieke A Hartman; Marieke B Snijder; Henriette Dijkshoorn; Ron J G Peters; Ellen Bal; Karien Stronks; Mary Nicolaou (PLoS ONE, 2021)
Objective Obesity is highly prevalent among ethnic minorities and acceptance of larger body sizes may put these ethnic minorities at risk of obesity. This study aimed to examine body size ideals and body satisfaction in relation to body weight, in two Sub-Saharan African (SSA)-origin groups in the Netherlands compared to the Dutch. Additionally, in the two SSA-origin groups, this study assessed the mediating role of acculturation in the relation between ethnicity and body size ideals and body satisfaction. Methods Dutch, African Surinamese and Ghanaians living in Amsterdam, the Netherlands, participated in the observational HELIUS study (n = 10,854). Body size ideals were assessed using a validated nine figure scale. Body satisfaction was calculated as the concordance of current with ideal figure. Acculturation was only assessed among SSA-origin participants and acculturation proxies included age of migration, residence duration, ethnic identity and social network. Weight and height were measured using standardised protocols. Results SSA-origin women and Ghanaian men had larger body size ideals compared to the Dutch; e.g. Surinamese and Ghanaian women had 0.37 (95%CI 0.32; 0.43) and 0.70 (95%CI 0.63; 0.78) larger body size ideals compared to Dutch women. SSA-origin participants were more often satisfied with their weight compared to the Dutch. Similarly, SSA-origin participants had more than twice the odds of being satisfied/preferring a larger figure compared to the Dutch (e.g. BSurinamese men 2.44, 95%CI 1.99; 2.99). Within the two SSA-origin groups, most acculturation proxies mediated the relation between ethnicity and body size ideals in women. Limited evidence of mediation was found for the outcome body satisfaction. Conclusion Public health strategies promoting a healthy weight may need to be differentiated according to sex and ethnic differences in body weight perception. Factors other than acculturation may underlie the ethnic differences between African Surinamese and Ghanaians in obesity.